The Association Between Family Supports and Middle Adult Hypertension Prevention Behavior - Dewi Amir, Mayasyanti; Kadila, Nur; bin Sansuwito, Tukimin (KnE Social Sciences, 2023)
One of the leading causes of death worldwide is hypertension. Indonesia still has a very low level of hypertension prevention awareness. Support from the family can help people prevent hypertension. Family support is a type of interpersonal interaction that involves accepting family members and having positive views toward them, so that they feel cared for. An action taken to avoid hypertension is called a hypertension preventative habit. This study aims to examine how family support and hypertension prevention behavior relate to one another in middle adulthood in the Baros ward, which is the service area for the Baros Public Health Center in Sukabumi City. This study has a cross-sectional design and is a correlational investigation. Cluster random sampling was used to collect data from 116 respondents in 8 hamlets in the Baros district. Collecting data using a questionnaire and bivariate analysis with Chi-square. The results of this study were 88 (75, 9%) respondents were known to have family support and as many as 67 respondents (76,1%) had good behavior in preventing hypertension. The results of Chi-square test showed p-value = 0.000 (< 0.05) indicating a connection between family support and hypertension prevention behavior in middle adulthood and it is hoped that this research will be an input for improving outreach programs about the importance of family support for hypertension prevention behavior. Keywords: family support, behavior, hypertension